Mental health disorders, functioning and health-related quality of life among extensively hospitalized patients due to severe self-harm – results from the Extreme Challenges project - Langjord, Tuva; Pedersen, Geir; Bovim, Tone; Christensen, Tore Buer; Eikenæs, Ingeborg Ulltveit-Moe; Hove, Oddbjørn; Kildahl, Arvid Nikolai; Mork, Erlend; Norheim, Astrid Berge; Ramleth, Ruth Kari; Ringen, Petter Andreas; Romm, Kristin Lie; et al. (Frontiers in Psychiatry, 2023)
Background Severe self-harm leading to extensive hospitalization generates extreme challenges for patients, families, and health services. Controversies regarding diagnoses and health care often follow. Most evidence-based treatments targeting self-harm are designed for borderline personality disorder (BPD). However, current knowledge about mental health status among individuals with severe self-harm is limited. Objectives To investigate psychopathology among patients extensively hospitalized due to severe or frequent self-harming behaviors. Method A cross sectional study (period 2019–2021) targeting psychiatric inpatients (>18 years) with frequent (>5) or long (>4 weeks) admissions last year due to self-harm. The target sample (N = 42, from 12 hospitals across all Norwegian health regions) was compared to individuals admitted to outpatient personality disorder (PD) treatment within specialist mental health services in the same period (N = 389). Clinicians performed interviews on self-harm and psychopathology, supplemented by self-report. Results The target sample were young adults, mainly female, with considerable hospitalization and self-harming behaviors, both significantly more extensive than the comparison group. The majority in both groups reported self-harm onset <18 years. The target sample reported increasing severity of self-harm acts and suicidal intention over time. Both samples had high levels of childhood trauma, impaired personality functioning, and a majority fulfilled criteria for PD. In the target sample, comorbid depression, PTSD, anxiety disorders, and substance use occurred more frequently and in 50%, psychosis/dissociative disorder/autism spectrum disorder/ADHD was reported (outpatient comparison sample: 9%). 35% in the target sample screened over cut-off for possible intellectual disability. The target sample reported poor psychosocial functioning and health-related quality of life – greater impairment than the outpatient comparison sample. Conclusion The study reveals that severe self-harm inpatients have complex psychopathology and highlights the importance of individualized and thorough assessment among patients with severe and/or repetitive self-harm.